2015
DOI: 10.1111/geb.12366
|View full text |Cite
|
Sign up to set email alerts
|

Extinction biases inQuaternaryCaribbean lizards

Abstract: Aim Intrinsic qualities that might affect extinction risk are not well understood for lizards (suborder Lacertilia), a highly diverse and globally distributed group of reptiles (order Squamata). We use the Quaternary fossil record of Caribbean lizards to explore a commonly studied trait, body size, and its relationship to extinction. Location The Caribbean. Methods We compiled a body size database for over 300 species. We assessed whether the present‐day body size distribution of lizards differed from the body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 49 publications
2
24
0
1
Order By: Relevance
“…While we acknowledge that the (sub-)fossil record is incomplete and can be biased towards particular regions, taxa or size classes (Steadman 2006, Boyer 2008, Duncan et al 2013, Kemp and Hadly 2015, our data provide a first comparative baseline for preserving and restoring plant-frugivore interactions on many islands. The underlying dataset (available from the Dryad Digital Repository) allows to identify particular frugivores and their ecological function (e.g.…”
Section: Implications For Conservation and Restorationmentioning
confidence: 99%
“…While we acknowledge that the (sub-)fossil record is incomplete and can be biased towards particular regions, taxa or size classes (Steadman 2006, Boyer 2008, Duncan et al 2013, Kemp and Hadly 2015, our data provide a first comparative baseline for preserving and restoring plant-frugivore interactions on many islands. The underlying dataset (available from the Dryad Digital Repository) allows to identify particular frugivores and their ecological function (e.g.…”
Section: Implications For Conservation and Restorationmentioning
confidence: 99%
“…As larger lizards have been demonstrated to have an elevated risk of extinction (Meiri, 2008;Tingley et al, 2013a;Kemp and Hadley, 2015), body size is seen as a proxy for life history traits (e.g., long-lived species with low clutch frequencies) that might inhibit a species' recovery from population declines. Furthermore, non-assessed lizard species were found to have smaller clutch sizes (corrected for female size), but equivalent longevity, to assessed species.…”
Section: Distributional Life History Ecological and Taxonomic Biasmentioning
confidence: 99%
“…Paleontological studies have identified patterns of size-biased vertebrate extinction in the Caribbean [53],[10], although we are still elucidating extinction chronologies for many taxonomic groups. Large-bodied terrestrial mammals such as ground sloths disappeared prior to the Ceramic period, potentially linked to hunting or habitat alteration [10].…”
Section: Introductionmentioning
confidence: 99%
“…This introduction of potential predators and competitors links both accidental and intentional species introductions to a major extinction event in the Caribbean mammals. Similarly, the disappearance of many lizards occurred after European arrival [53],[49], likely due to impacts from introduced species.…”
Section: Introductionmentioning
confidence: 99%